Mnemonic Hauntings: Photography as Art of the Missing - Tandeciarz, Silvia (Social justice, 2006)
Part of a special issue on art, power, and social change. The writer explores the uses of photography in post-dictatorship Argentina. The military regime that ruled Argentina between 1976 and 1983 committed countless human rights abuses in the name of national security, with human rights groups estimating the total number of victims to be 30,000. In contemporary Argentina, “common memory” acknowledges the brutality of the dictatorship as part of it recent past, but official rhetoric has tried to close off the period, suggesting that it is contained within the past and that it is finished and should be forgotten in order to move forward and achieve stability. The writer contends that photography, notably the work of Marcelo Brodsky, has proved effective in resisting this discourse and maintaining the negotiation between the past and its legacy in contemporary Argentina.